Thyroglossal Duct Fistula with an Unusual Presentation: A Case Report - Gyawali, Bigyan R; Dutta, Heempali; Tripathi, Prashant (Journal of Institute of Medicine Nepal, 2019)
Thyroglossal duct anomaly is one of the commonest congenital anomalies with midline neck manifestation. Though commonest location mentioned in the literature is thyrohyoid, several rare presentations have also been described. Here, we present a very rare case of thyroglossal fistula manifesting in submental region.